Stocking density optimisation for gulsha, Mystus cavasius farming in pond under drought prone area of Bangladesh - Sabuz, Shovan Khan; Khan, Md. Imran; Hossain, Md. Akhtar (Journal of Fisheries, 2024)
Lack of appropriate stocking density is the constraint for aquaculture promotion of a potential species like gulsha, Mystus cavasius in ponds under drought prone area. With a view to addressing this problem, three different densities 98800, 123500 and 148200 gulsha individuals ha–1 were tested under three treatments (T1, T2 and T3) in ponds under Paba Upazila of Rajshahi district, Bangladesh. Treatments were replicated thrice. Hatchery produced gulsha seeds were grown for a period of six months from July – December 2021 with commercial feed containing 35% protein. Water quality and fish growth were monitored fortnightly. Significantly (p < 0.05) lowest value of dissolved oxygen and highest values of carbon di-oxide and ammonia-nitrogen were observed in T3. Significantly lowest values of final weight, weight gain, specific growth rate and survival rate were also observed in T3. However, significantly (p < 0.05) highest yield and cost-benefit ratio were obtained in T2.